2022
DOI: 10.1002/cssc.202201205
|View full text |Cite
|
Sign up to set email alerts
|

Doping Mo into NiFe LDH/NiSe Heterostructure to Enhance Oxygen Evolution Activity by Synergistically Facilitating Electronic Modulation and Surface Reconstruction

Abstract: It is of great significance to design highly efficient electrocatalysts with abundant earth elements instead of precious metals for water splitting. Herein, Mo‐doped NiFe‐layered double hydroxides/NiSe heterostructure (Mo‐NiFe LDH/NiSe) was fabricated by coupling Mo‐doped NiFe LDH and NiSe on nickel foam (NF). The heterostructure electrocatalyst showed ultra‐low overpotential (250 mV) and remarkable durability for oxygen evolution reaction (OER) at 150 mA cm−2. Both theoretical and experimental results confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…In addition, prior literature also suggest that Mo doping could induce redistribution of the surface electron density to accelerate charge transfer and promote the formation of the *OOH intermediate for NiFe LDH structures as well. 11,68,71,75 Congruent with these prior observations, NN-12 also exhibits significantly lower charge transfer resistance ( R ct ) than the original NiFe LDH, 39 as observed from electrochemical impedance spectroscopy (Fig. S5.4, ESI†).…”
Section: Resultssupporting
confidence: 74%
“…In addition, prior literature also suggest that Mo doping could induce redistribution of the surface electron density to accelerate charge transfer and promote the formation of the *OOH intermediate for NiFe LDH structures as well. 11,68,71,75 Congruent with these prior observations, NN-12 also exhibits significantly lower charge transfer resistance ( R ct ) than the original NiFe LDH, 39 as observed from electrochemical impedance spectroscopy (Fig. S5.4, ESI†).…”
Section: Resultssupporting
confidence: 74%
“…It can be clearly observed that there is an obvious response to the oxygen evolution reaction process for the S-NiFeV LDH electrode in 1.0 M KOH solution without urea, which originates from the oxidation peak of the Ni species (Ni 2+ /Ni 3+ ). 54–57 Depicted in Fig. 5(b) are the LSV curves of the S-NiFeV LDH, NiFeV LDH, and NiFe LDH for the UOR, along with those of the commercial RuO 2 and bare NF as a contrast.…”
Section: Resultsmentioning
confidence: 99%
“…metals endows heteroatom-doped compounds with uncommon catalytic activity due to the unusual d-band electron complementary effect. [37][38][39] Encouraged by the above, coordinating nickel selenide by Mo doping and simultaneously modulating accessible micro/nanostructures seem to be an effective strategy to further improve IRR activity.…”
Section: Introductionmentioning
confidence: 99%